Leadership Style and Business Performance in Nepali SMEs: The Mediating Role of Entrepreneurship Orientation (Journal of Business and Management Research, 2020)
Leadership and entrepreneurship, and their effects on business performance are major issues in contemporary academic research as they are linked with economic development of a nation. However, relatively only a few studies have been carried out on the relationship among these three variables with even less attention paid to entrepreneurship orientation (EO) serving as a mediator in leadership-performance relationship. This study firstly tested the relationship between leadership style and business performance and then analyzed the mediating role of EO between them in the Nepali SMEs. The study utilized 188 responses collected from business owners in Pokhara, Nepal. Findings suggest that transformational and transactional leadership style as well as EO exert significant positive influence over business performance. The study indicates that transformational leadership is stronger predictor of EO and business performance than transactional leadership style. It also found that EO mediates transformational leadership-performance relationship. The implications, limitations, and suggestions have been identified and discussed.